2022
DOI: 10.3390/sexes3040038
|View full text |Cite
|
Sign up to set email alerts
|

How Context Matters: Change and Persistence of Homophobic Attitudes among Cameroonian Migrants in Switzerland

Abstract: Debates on human rights in recent years have brought to the fore stark fault lines between African countries, where societal intolerance towards homosexuality is prevalent, and Western countries, which hold more tolerant views towards homosexuality. As contention rages around African identity and homosexuality, one interesting question calls for attention: how do the attitudes of Africans towards homosexuality evolve—or not—when they migrate from their home context to a more open society where homosexuality is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In researching attitudes towards homosexuality among Cameroonians based at home and in Switzerland, I made use of surveys, interviews, and focus group discussions to assess levels of homophobia within the two groups [56]. Though instrumental in achieving my research goals, these traditional methods were insufficient to capture my everyday research experiences [52].…”
Section: Autoethnography As Methodsmentioning
confidence: 99%
“…In researching attitudes towards homosexuality among Cameroonians based at home and in Switzerland, I made use of surveys, interviews, and focus group discussions to assess levels of homophobia within the two groups [56]. Though instrumental in achieving my research goals, these traditional methods were insufficient to capture my everyday research experiences [52].…”
Section: Autoethnography As Methodsmentioning
confidence: 99%
“…Homophobic violence is a major problem facing many Societies (Lyonga, 2022). They are extreme manifestations of heteronormative socio-cultural practices.…”
Section: The Perceived Threat Of Homosexuality and Violence Against L...mentioning
confidence: 99%
“…This report indicated that for 84% of Cameroonians, their country was not a good place to live for members of the LGBTQ community. By way of illustration, we can cite the sentencing, in April 2011, of a man named Roger Mbédé to thirty-six (36) months in prison for having sent another man an SMS in which he declared that he was in love with him (Lyonga, 2022;Messanga and Sonfack, 2017); the murder of gay rights activist Eric Lembembe in July 2013 (Messanga and Sonfack, 2017); or more recently, the sentencing, in May 2021, of two transgender people to five (5) years in prison. They had been arrested by the security forces because they were dressed in a typically feminine way despite their biological sex being male (hrw.org/fr/news/2021/05/12/in cameroon two women transgender people were sentenced five years in prison).…”
Section: The Perceived Threat Of Homosexuality and Violence Against L...mentioning
confidence: 99%
See 2 more Smart Citations